Nieznane drobiny epistolarne Stanisława Wyspiańskiego - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The work concerns two short letters by Stanisław Wyspiański, which haven’t been published before. The letters, adressed to Maria Siedlecka and Eliza Pareńska, seem to be important in context of the artist’s biography.